(untitled) (Baghdad Science Journal, 2010)
The study included the extraction of volatile oil from Mentha piperita which was 1.3 % in the leaves and flowers . Volatile oil of the Mentha piperita leaves had special aromatic odour, pale yellow color, slightly pungent taste . The specific gravity and refractive index were (0.9794) and ( 1.464) respectively. The inhibition activity of the Mentha piperita Volatile oil extracts were studied on some pathogenic microorganisms like Staphylococcus aureus, Salmonella typhi, Escherichia coli, Proteus sp, and Klebsiella pneumoniae . The result showed that the volatile oil had an inhibition effect on the growth of all microorganisms, and it gave the higher inhibition effect on the growth of S. aureus in which the inhibition zone reached to 25 mm. also the inhibition zoon on the growth of K. pneumoniae was 20 mm.and it was 17 mm. on the growth of Salmonella.typhi , while the effect was slight on the growth of Proteus sp and E. coli 12,10 mm. respectively. The minimum inhibition concentration (MIC) and the minimum bactericidal concentration (MBC) of the volatile oil extract of the Mentha .piperita leaves, were determined. The value of (MIC, MBC) of Staph. aureus was 0.625 , 1.25 % and the value for (MIC, MBC) of K. pneumoniae? Salmonella typhi were 1.25 , 2.5 % for each of them, while the value of (MIC, MBC) of Proteus sp , E. coli were 2.5 , 5 % respectively .